Lithuanian Sources of the Belarusian Expressions of atósa and atós - Smoczyński, Wojciech (Slavistica Vilnensis, 2018)
[full article, abstract in Polish; abstract in Lithuanian and English]The Belarusian words atósa and atós (‘iron rod or rope connecting the axle of the front wheels with the shaft’) are not due to the reshaping of the Lithuanian loanword atãsėja id., as has been hitherto assumed. These words were borrowed from the East Lithuanian dialect, where the forms atasà and atãsas have been recently uncovered and the phonetic correspondence to the Belarusian imports of whose is exact. The difference between atãsėja and atasà/atãsas is due to an East Lithuanian innovation: atãsėja was metanalyzed as atas-ėja and was then subject to backformation, which produced two variant dialectal reflexes: atas- + -a and atas- + -as.
Keywords: Belarusian, Lithuanian, metanalysis, backformation